(untitled) (Eurasian Journal of Ecology, 2021)
About the remains of Ichthyosaurs of the genus Nannopterigius from the Late jurassic of West Kazakhstan region. This article discusses the discovery of the remains of an ichthyosaur of the genus Nannopterygius from the territory of the West Kazakhstan region of the Republic of Kazakhstan. As scientific researches show, fragments of skeletons of representatives of the genus are often found in deposits of the Late Jurassic at the site of Pogodaevo of the Baiterek district of the West Kazakhstan region. Described specimen has various diagnostic features of the structure of individual skeletal fragments (width of the interclavicle platform, length-to-width ratio of the coracoid, width of the distal end of the scapula). The aim of the study is to study the variability in the structure of skeletal fragments based on new finds of an ichthyosaur of the genus Nannopterygius (Yasykovia). In this article, the generally accepted paleontological methods of field and desk research were applied: the standard method of working with paleontological material to extract the studied samples from the host rock; morphological and morphometric analysis of fossils during species diagnostics. The presence of ichthyosauric remains similar to the holotype Nannopterygius (Yasykovia) yasykovi has been confirmed in the Jurassic deposits of the Republic of Kazakhstan. Material from Nannopterygius (Yasykovia) shows significant individual variability in skeletal structure. The age of the find belongs to the Late Jurassic, Upper Volga sub-stage, Epivirgatites nikitini zone Key words: Nannopterygius (Yasykovia), Western Kazakhstan, Late Jurassic, Upper Volga substage.